Analysis of Basic Transportation Rates for Public Transport (Angkot) (Case Study in Route of Central Market - Minasa Upa) - THOENGSAL, JAMES (Kirana Publisher (KNPub), 2023)
Analysis of public transport tariffs is one of the supporting factors for public transportation for the general Makassar community. Especially people who use transportation transportation services on the Central Market route - Minasa Upa or vice versa. The purpose of this research is to obtain a detailed description of the analysis of the costs of the Central Market public transport route - Minasa Upa in Makassar City and analyze public transport fares on Central Market routes - Minasa Upa and from Minasa Upa - Central Market. The data collection method used in this study was conducted by conducting interviews and questionnaire distribution to the public transportation management (Angkot) routes of the Central Market-Minasa Upa. The calculation results of Central Market transport rates - Minasa Upa which consists of two types of vehicles, namely, Suzuki Carry 1500 cc produces a basic tariff for public transportation of Rp. 4000, - / Route and Student Transportation Tariff of Rp. 2600, - / Route, while for the type of Daihatsu Grand Max 1500 cc, the basic tariff for public transportation is Rp. 5000, - / Route and student transportation tariff of Rp. 3400, - / Route